2013
DOI: 10.5588/ijtld.12.0635
|View full text |Cite
|
Sign up to set email alerts
|

Pleural cancer antigen-125 levels in benign and malignant pleural effusions

Abstract: CA-125 levels in benign pleural effusions may not be influenced by pleural inflammation or hydrostatic or oncotic pressure changes. Pleural CA-125 levels may not be influenced by the histological type of tumour in malignant pleural effusions, suggesting that mesothelial cell properties may not be altered by these factors in the pleural space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Choi et al . 23 found that pleural CA-125 levels were significantly higher in malignant pleural effusions than those in benign pleural effusions. Bielsa et al .…”
Section: Discussionmentioning
confidence: 87%
“…Choi et al . 23 found that pleural CA-125 levels were significantly higher in malignant pleural effusions than those in benign pleural effusions. Bielsa et al .…”
Section: Discussionmentioning
confidence: 87%
“…By way of a solution to these problems, measuring the concentration of various tumor markers (TMs) in PE is a useful and noninvasive procedure for distinguishing between benign PE and MPE. [ 5 6 7 ] The TMs concerned are carbohydrate antigen 125 (CA125), carbohydrate antigen 153, carbohydrate antigen 199 (CA199), carcinoembryonic antigen (CEA), cytokeratin 19 fragment, neuron-specific enolase (NSE), and squamous cell carcinoma (SCC) associated antigen. However, their cut-off values and sensitivities in identifying MPE are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…in the pleural fluid did significantly differ (p < 0.001) Choi et al (2013). determined Ca-125 levels in pleural puncture fluid of 326 patients and afterwards retrospectively analysed its level in patients with various aetiology of the pleural fluid.…”
mentioning
confidence: 99%